Migration of Graduates within a Sequential Decision Framework: Evidence from Poland - Mikolaj Herbst; Pawel Kaczmarczyk; Piotr Wojcik (Institute for the Study of Labor (IZA), 2014)
According to the economic literature human capital is a critical growth factor. This is why migration of individuals well endowed with human capital is subject of interest for both academics and policymakers. The aim of this paper is to identify main drivers of highly skilled migration within Poland. Following the findings of earlier studies, we argue that the spatial mobility of individuals should not be considered in terms of one-time displacement, but rather as a sequence of migration decisions within certain time period. We assume that the propensity to migrate depends on factors to be interpreted in terms of aspirations and capabilities and, additionally, the importance of those factors can change during the education process and in the life course. Applying multinomial logit modelling on the unique database on Polish graduates we find that all tested migration strategies can be explained both in terms of capacities to aspire and capacities to realize, whereas repeat migration is driven particularly by characteristics related to level of aspirations and return migration - by low capacities to realize the migration projects.
Keywords: I25; J24; J61; J62; 330; high skilled migration; graduates; sequential decision framework; capacity to aspire; capacity to realize